Non-COVID-19 emergencies: where have all the patients gone? - Boeken, Tom (Eur Radiol, 2020)
• Early in the pandemic, numbers of patients undergoing non-COVID-19 emergent CTs dropped sharply but diagnostic yield did not increase, suggesting potentially undiagnosed emergencies in patients not seen in healthcare institutions.